PERAN JOGJA LIBRARY CENTER DALAM MELESTARIKAN BUDAYA LOKAL - Annisa Diansari; Wafiq Alfia Fadhliati; Mega Alif Marintan (2025)
This study aims to determine the role of the Jogja Library Center (JLC) in preserving and strengthening local cultural resilience in the face of globalization challenges. As one of the public library institutions under the auspices of the Yogyakarta Special Region Library and Archives Office, JLC has great potential to maintain cultural values through the provision of documentary collections, educational activities, and cultural literacy services. The method used in this research is qualitative, employing a narrative research approach, which involves conducting interviews and observations of librarians and the JLC environment. The results showed that JLC has contributed significantly to the preservation of local culture, among others through the collection of newspapers, magazines, manuscript surgery, and Javanese script training. Nevertheless, JLC still has a great opportunity to strengthen its role through external collaboration with literacy communities, educational institutions, and tourism agencies. This study recommends the development of strategic cooperation as a concrete step to increase the reach and effectiveness of cultural preservation programs by the JLC.